PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI CV HASTANINGRAT JOMBANG - Al ‘ izzahtu Amalia; Lik Anah (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the effect of leadership and work environment on employee job satisfaction at CV Hastaningrat Jombang. The method used in this study is a quantitative research method. The population in this study were 36 respondents. The sampling technique is to use a saturated sample technique which makes the entire popuilation as a samplei. Thei reisuilts of thei stuidy show that: (1) Leiadeirship partially has a positivei and significant eiffeict on job satisfaction variableis at CV Hastaningrat Jombang, (2) Work einvironmeint has a significant eiffeict on job satisfaction variableis at CV Hastaningrat Jombang, (3) Leiadeirship and work einvironmeint simuiltaneiouisly havei an eiffeict significant to thei job satisfaction variablei at CV Hastaningrat Jombang